O desafio da atividade física em usuários com dor lombar na atenção primária - Menezes, Roberta Mendes de (2019)
Introduction: Low back pain (LBP) is the most disabling health condition, with a prevalence of approximately 50% in the Brazilian population. The practice of physical activity, especially of leisure, has been increasingly studied in individuals with chronic LBP (CLBP). Physical deconditioning, in combination with social and emotional factors, are possible compromising factors to CLBP recovery. Aim: To identify the physical activity profile of users with CLBP attended in primary care. Methodology: We recruited for this study residents from Region III of Fortaleza, assisted by the Movement Extension project from Universidade Federal do Ceará (UFC). Participants answered questionnaires regarding sociodemographic factors, pain, disability and their level of physical activity (IPAQ - short version). Results: These results are from 110 participants, aged 56.6 (± 13.53) years; of those, 82% were female, and approximately 50% had a low level of schooling. Pain intensity was 4.53 (± 2.98) and disability profile was 11.56 (± 5.76) points. The majority of the users had high (46.3%) or moderate (25.4%) levels of physical activity. However, 56.35% did not perform any type of physical exercise. Among the practitioners of exercise, walking was the most reported modality (52.3%). Conclusion: The findings indicate that, despite there is a group reporting high levels of physical activity, it is necessary to insert approaches that prioritize the practice of leisure physical activities, including physical exercises in individuals with CLBP. In addition, it is suggested that a walking program can be used as a low cost strategy in primary care.